Migration between Southeast Asia and Taiwan: Trends, Characteristics and Implications - Tsay, Ching-lung (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2015)
The migration of human resources between Southeast Asia and Taiwan is significant, indicating a close bilateral relationship. This study takes the perspective of economic development to examine the migration flows, aiming to explore the migration impacts of differences in societal development. Based on the Taiwan-Southeast Asia relative development status, the study further theorizes the possible migration trends between the two places. Empirically, the investigation focuses on major types of migration from Indonesia, the Philippines, Thailand, and Vietnam to Taiwan, including contract workers, immigrant spouses, professionals and the skilled, as well as students. The Taiwan to Southeast Asia migration covers mainly those migrants induced by Taiwanese investment. According to available information, the migration between Taiwan and Southeast Asia is rather asymmetric, with the Southeast Asia to Taiwan flows far more important than the counter flows. This fact indicates an advantageous position for Taiwan to cultivate relations with the migrant sending nations. It also provides a niche for every source country to work closely with Taiwan in migration management and migrant protection, for the interests of both the places of origin and destination.